ANALISIS USAHATANI BEBERAPA VARIETAS UNGGUL PADI SAWAH DI KABUPATEN LABUHANBATU - Nasution, Yusri Indra; Lubis, Zulkifli; Rahman, Abdul (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2019)
This study aims to determine the differences in production, revenue, income differences and the feasibility of Ciherang, Inpari 13 and Mekongga rice fields in the study area. To determine the feasibility of Ciherang, Inpari 13 and Mekongga varieties of rice farming, it is feasible from the comparison of revenue and costs in the study area. To find out the efficiency of Ciherang, Inpari 13 and Mekongga varieties in the study area. The average income of paddy farming received by respondent farmers in Labuhanbatu Regency for Ciherang variety is Rp. 14,416,111.11, - per Ha / MT. A Return Cost Ratio (R / C ratio) of 2.29 shows that R / C 1, then this farm is profitable. The biggest acceptance for lowland rice farming in Labuhanbatu Regency was Ciherang variety, followed by Inpari 13 variety, and the lowest acceptance was Mekongga Variety. The R / C ratio indicates that it is still feasible to be cultivated, but in terms of the BEP value of land use, the number shown 1, means that land tenure below 1 Ha will not be able to sustain farmers' income if there is a 10% increase in total production costs with the assumption of production and fixed price (no increase).